Analysis of Fashion Trends of the Range Children's Clothing - Allakulov B.R; Tohirova A.Sh; Bazarbayeva G.G (Periodica Journal, 2022)
The structure of the assortment of children's clothing is very diverse in terms of purpose, materials used, manufacturing technology, types, shape, cut, colors, finishes, etc., which is due to the peculiarities of the physical, psychological and physiological development of children at different ages. Fashion in clothes for children is manifested indirectly. There are no such frequent and abrupt changes in forms, silhouettes and volumes. The designs and volumes of children's clothing are more stable than those of adults, and the influence of time and fashion is felt mainly in the details and finishes
Keywords: manufacturing technology; types; shape; cut